Evaluación de la calidad de vida mediante el cuestionario EORTC QLQ-C30 en pacientes con cáncer en cuidados paliativos - Castillo Alva, Roque Cristhian (2017)
To determine the life quality of cancer patients in palliative care treated at the "Instituto Regional de Enfermedades Neoplasicas", as well as the association between life quality with age, sex, educational level, civil status, employment situation and economic situation. METHODOLOGY: An observational, descriptive, cross-sectional study was conducted in patients with cancer in palliative care. RESULTS: The sample study consisted of 49 patients, the predominant cancer was the cervix in the female and prostate in the male, the average overall score of the EORTC QLQ-C30 questionnaire was 64.3 points, a p value was found at Associate the quality of life with each one of the variables age (p=0.006), education (p<0.05), marital status (p=0.018), labor (p=0.019) and economic (p=0.002); which indicates that they are statistically significant CONCLUSION: The life quality of cancer patients in palliative care treated in IREN-NORTE is good and there is an association between life quality with the variable age, education, marital status, employment, academic